A preparation process of polyvinyl alcohol and nitrile latex composite foam and its modification method
By using chitosan and tannin as modifiers for composite foam of polyvinyl alcohol and nitrile latex, a modified foam with high adsorption capacity is formed, and the problem of insufficient adsorption capacity of PVA foam in the prior art is solved, and effective reduction of water pollution is achieved.
Patent Information
- Application Number
- CN202411309612.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-09-19
Smart Images

Figure CN119119567B_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a preparation process of polyvinyl alcohol and nitrile latex composite foam and a modification method thereof. Background Art
[0002] In the textile industry, the discharge of large amounts of high-concentration reactive dyes into the aquatic environment is one of the main causes of water pollution. Among them, methylene blue (MB), methyl orange (MO) and rhodamine B (RB) are three commonly used dyes in the textile industry. They are considered to be carcinogenic and mutagenic, and pose a potential threat to ecosystems, biological organisms and humans. Therefore, it is necessary to purify the aquatic environment and reduce dye pollution. There are many purification technologies at present, each with its own advantages and disadvantages.
[0003] Among them, adsorption has attracted wide attention from industry and academia as a low-cost and promising purification scheme, and foam adsorption is often used for the purification of three dyes: methylene blue (MB), methyl orange (MO), and rhodamine B (RB);
[0004] Currently commonly used foams include polyvinyl alcohol (PVA) foams, but the adsorption mechanism of PVA foams for the above dyes is unclear, and it is difficult to obtain PVA-based foam materials with high adsorption capacity, resulting in the inability to fully absorb methylene blue, methyl orange, and rhodamine B. Water pollution is still serious and urgently needs to be improved.
[0005] Therefore, it is necessary to invent a preparation process of polyvinyl alcohol and nitrile latex composite foam and a modification method thereof to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation process of polyvinyl alcohol and nitrile latex composite foam and a modification method thereof. The polyvinyl alcohol and nitrile latex composite foam is modified by using chitosan and tannic acid as modifiers to obtain a modified foam capable of adsorbing multiple dyes and having a strong adsorption capacity. The modified foam can well adsorb MB, MO, and RB reactive dyes in wastewater, thereby reducing water pollution and having good application prospects. The chitosan and tannic acid blended solution is used as a modifier, which can tightly adhere to the surface of the polyvinyl alcohol and nitrile latex composite foam without clogging the pores, allowing liquid to flow inside the polyvinyl alcohol and nitrile latex composite foam. That is, the modifier has good binding properties with the polyvinyl alcohol and nitrile latex composite foam, so that the adsorption capacity of the obtained modified foam is significantly improved, thereby greatly reducing water pollution in the textile industry, being conducive to green development, and solving the above-mentioned deficiencies in the technology.
[0007] In order to achieve the above object, the present invention provides the following technical solution: a preparation process of polyvinyl alcohol and nitrile latex composite foam, comprising the following steps:
[0008] Step 1, add polyvinyl alcohol and deionized water into a beaker, stir and cool to room temperature to prepare a polyvinyl alcohol solution for standby use;
[0009] Step 2, add polyvinyl alcohol solution and nitrile latex to another beaker, stir, and cool to room temperature after the reaction is completed to prepare a blended solution;
[0010] Step 3, adding sodium dodecyl sulfate to the blended solution, stirring and foaming, and then pouring into a silica gel mold and freezing to prepare a sample;
[0011] Step 4: Thaw the sample in anhydrous ethanol, and then dry it to obtain a composite foam of polyvinyl alcohol and nitrile latex.
[0012] In the above-mentioned preparation process of the composite foam of polyvinyl alcohol and nitrile latex, in step 1, the polyvinyl alcohol is 10 g, the deionized water is 80 g, and the mixture is stirred at 95° C. for 2 hours using a magnetic rotor.
[0013] In the preparation process of the aforementioned polyvinyl alcohol and nitrile latex composite foam, in step 2, the stirring time is set to 1 hour, and the amount of polyvinyl alcohol solution added is 30g, 40g, 50g, 60g or 70g, and the amount of nitrile latex added is 70g, 60g, 50g, 40g or 30g.
[0014] In the preparation process of the aforementioned polyvinyl alcohol and nitrile latex composite foam, in step 3, an IKA digital display stirrer is used to stir and foam for 5 minutes at 1200 rpm, the freezing temperature is -20°C, and the freezing time is 24 hours.
[0015] In the above-mentioned preparation process of polyvinyl alcohol and nitrile latex composite foam, in step 4, the thawing time is 12 hours, the drying temperature is 50° C., and the drying time is 24 hours.
[0016] A method for modifying a polyvinyl alcohol and nitrile latex composite foam comprises the following steps:
[0017] Step A, adding chitosan powder into deionized water containing glacial acetic acid and stirring to prepare a chitosan solution;
[0018] Step B, adding tannic acid into deionized water to dissolve it to prepare a tannic acid solution;
[0019] Step C, mixing the tannic acid solution and the chitosan solution, and cooling to room temperature to prepare a modifier for standby use;
[0020] Step D: immerse the composite foam of polyvinyl alcohol and nitrile latex in a modifier, squeeze it repeatedly, let it stand, and dry it to obtain a modified foam.
[0021] In the modification method of the polyvinyl alcohol and nitrile latex composite foam, in step A, the chitosan powder is 2 g, the glacial acetic acid is 2 mL, the deionized water is 100 mL, the stirring temperature is 50° C., and the stirring time is 2 h.
[0022] In the above-mentioned modification method of polyvinyl alcohol and nitrile latex composite foam, in step B, tannic acid is 0.6 g, deionized water is 100 mL, and the temperature is room temperature.
[0023] In the aforementioned modification method of polyvinyl alcohol and nitrile latex composite foam, in step C, the stirring temperature is 50° C. and the stirring time is 0.5 h.
[0024] In the modification method of the polyvinyl alcohol and nitrile latex composite foam, in step D, the extrusion times are 3 times, the interval time is 6 hours, the standing time is 12 hours, the drying temperature is 50° C., and the drying time is 12 hours.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention prepares a composite foam of polyvinyl alcohol and nitrile latex by using polyvinyl alcohol and nitrile latex, and then uses chitosan and tannic acid as modifiers to modify the composite foam of polyvinyl alcohol and nitrile latex, and finally obtains a modified foam capable of adsorbing a variety of dyes and having a strong adsorption capacity. The modified foam can well adsorb MB, MO, and RB active dyes in wastewater, has a significant effect on purifying the water environment, reduces water pollution, and has good application prospects.
[0027] 2. The present invention adopts chitosan and tannic acid blend solution as a modifier, which can adhere tightly to the surface of the polyvinyl alcohol and nitrile latex composite foam without clogging the pores, allowing liquid to flow inside the polyvinyl alcohol and nitrile latex composite foam, that is, the modifier has good binding properties with the polyvinyl alcohol and nitrile latex composite foam. After modification by the modifier, a PVA-based foam material with high adsorption capacity, that is, a modified foam, can be obtained, thereby greatly reducing the pollution of MB, MO, and RB to the water environment in the textile industry, which is conducive to green development. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0029] Figure 1 The process flow chart of producing polyvinyl alcohol and nitrile latex composite foam of the present invention;
[0030] Figure 2 The process flow chart of producing modified foam of the present invention;
[0031] Figure 3 In the figure, Figure a is the SEM image of the composite foam of polyvinyl alcohol and nitrile latex;
[0032] Figure b is the SEM image and high magnification SEM image of the composite foam of polyvinyl alcohol and nitrile latex when the ratio of polyvinyl alcohol to nitrile latex is 30:70;
[0033] Figure 4 This is the EDS analysis diagram of the composite foam of polyvinyl alcohol and nitrile latex and the modified foam;
[0034] Figure 5 This is the surface distribution diagram of C, N and O elements in the composite foam of polyvinyl alcohol and nitrile latex and the modified foam;
[0035] Figure 6 The infrared spectra of tannic acid, chitosan, tannic acid and chitosan, polyvinyl alcohol and nitrile latex composite foam and modified foam are shown;
[0036] Figure 7 It is a line graph of the adsorption of three dyes (MB, MO, RN) by modified foams at different ratios of polyvinyl alcohol to nitrile latex;
[0037] Figure 8 It is a line graph of the adsorption of three dyes by modified foams with different tannic acid contents;
[0038] Fig. 9 It is a line graph of the adsorption of dyes by the composite foam of polyvinyl alcohol and nitrile latex, and the modified foam when the initial concentrations of the three dyes are different;
[0039] Fig.10 It is a line graph of the adsorption of dyes by polyvinyl alcohol and nitrile latex composite foam and modified foam at different temperatures;
[0040] Fig.11 It is the line graph of the adsorption of three dyes by the modified foam at different pH values;
[0041] Fig.12 It is a line graph of the adsorption of dyes by polyvinyl alcohol and nitrile latex composite foam and modified foam at different contact times. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0043] In the present application, polyvinyl alcohol (PVA) is a polymer foam material, which is light and porous, has a high porosity and specific surface area, and has abundant free hydroxyl (-OH) and acetic acid (-O-CO-CH3) groups on the polymer chain, and can be used as an adsorbent for anionic and cationic dyes;
[0044] Nitrile latex (NBR) is a latex made by emulsion polymerization of butadiene and acrylonitrile. It has excellent oil resistance and chemical resistance. The cyanide (-CN) it contains is highly active and can react with a variety of substances. It can also absorb cationic dyes.
[0045] Chitosan (CS), as a biopolymer, has abundant hydroxyl and amino groups, high adsorption potential, and great advantages in dye adsorption;
[0046] Tannic acid (TA) is a natural polyphenol that contains special functional groups, carbonyl and phenolic hydroxyl, which can undergo cross-linking reactions with the amino groups on the CS chain through Schiff base reaction or Michael addition, while improving the mechanical strength and adsorption properties of CS.
[0047] In view of this, the present invention provides Figure 1-12 The preparation process of a polyvinyl alcohol and nitrile latex composite foam shown comprises the following steps:
[0048] Step 1, add 10g polyvinyl alcohol and 80g deionized water into a beaker, stir at 95°C for 2 hours using a magnetic rotor, and then cool to room temperature to prepare a polyvinyl alcohol solution for standby use;
[0049] Step 2, add polyvinyl alcohol solution and nitrile latex to another beaker, stir for 1 hour, and cool to room temperature after the reaction to prepare a blended solution;
[0050] Wherein, the amount of polyvinyl alcohol solution added is 30g, 40g, 50g, 60g or 70g, and the corresponding amount of nitrile latex added is 70g, 60g, 50g, 40g or 30g;
[0051] Step 3, adding sodium dodecyl sulfate to the blended solution, stirring and foaming for 5 min at 1200 rpm using an IKA digital stirrer, pouring into a silicone mold, and freezing at -20°C for 24 h to prepare a sample;
[0052] Step 4: Thaw the sample in anhydrous ethanol for 12 hours, and then dry it at 50° C. for 24 hours to obtain a composite foam of polyvinyl alcohol and nitrile latex.
[0053] A method for modifying a polyvinyl alcohol and nitrile latex composite foam comprises the following steps:
[0054] Step A, adding 2 g of chitosan powder into 100 mL of deionized water containing 2 mL of glacial acetic acid, mixing and stirring at 50° C. for 2 h to prepare a chitosan solution;
[0055] Step B, adding 0.6 g of tannic acid into 100 mL of deionized water and dissolving it at room temperature to prepare a tannic acid solution;
[0056] Step C, mixing and stirring the tannic acid solution and the chitosan solution at 50° C. for 0.5 h, cooling to room temperature, and preparing a modifier for standby use;
[0057] Step D: immerse the composite foam of polyvinyl alcohol and nitrile latex in a modifier, repeatedly squeeze it 3 times at an interval of 6 hours, let it stand for 12 hours, and then dry it at 50° C. for 12 hours to obtain a modified foam.
[0058] Verification experiment
[0059] The prepared polyvinyl alcohol and nitrile latex composite foam and modified foam were subjected to pore morphology analysis, EDS element analysis, infrared spectrum analysis, and adsorption performance analysis. The experimental results are as follows: Figure 3-12 As shown;
[0060] 1. Analysis of cell morphology
[0061] like Figure 3 As shown in Figure a, 30:70 means that the amount of polyvinyl alcohol solution added is 30g, and the amount of nitrile latex added is 70g, and the same applies to 40:60, 50:50, 60:40, and 70:30;
[0062] from Figure 3 As can be seen from Figure a in the figure, the pore size of the polyvinyl alcohol and nitrile latex composite foam is not uniform. It is composed of large and small pores. The pores are interconnected, allowing liquids such as water to remain in them. As the number of nitrile latex decreases, the pore size also decreases, the pore density increases, and the pore size becomes more uniform, but the pore wall becomes thicker. At the same time, the polyvinyl alcohol and nitrile latex composite foam shows phase separation in the high-power SEM image, and the surface becomes rough. At 30:70, the polyvinyl alcohol and nitrile latex composite foam has a higher porosity, and polyvinyl alcohol and nitrile latex have the best compatibility. Therefore, when modifying the polyvinyl alcohol and nitrile latex composite foam, the selected ratio of polyvinyl alcohol to nitrile latex is 30:70. Figure 3 As shown in Figure b, chitosan and tannic acid mainly adhere to the surface of the foam and do not block the pores, nor hinder the immersion of liquid. There is no obvious phase separation under the high-magnification SEM image, indicating that chitosan and tannic acid have good adhesion to the composite foam of polyvinyl alcohol and nitrile latex.
[0063] 2. About EDS element analysis
[0064] Depend on Figure 4 It can be seen that the nitrogen content of the modified foam is lower than that of the composite foam of polyvinyl alcohol and nitrile latex before modification, while the oxygen content is increased. This is because the latex molecular chain of nitrile latex contains a large number of cyano groups, which itself contains nitrogen. The nitrogen content in chitosan is low, and the carbon and oxygen content are high. Tannic acid and chitosan adhering to the foam surface will reduce the nitrogen content of the modified foam.
[0065] And by Figure 5 It can be seen that compared with the composite foam of polyvinyl alcohol and nitrile latex, the density of carbon, nitrogen and oxygen elements on the surface of the modified foam modified by chitosan and tannic acid is increased, which indicates that the modifier successfully adheres to the surface of the composite foam of polyvinyl alcohol and nitrile latex and is tightly combined with the composite foam of polyvinyl alcohol and nitrile latex.
[0066] 3. About infrared spectroscopy analysis
[0067] Depend on Figure 6 As shown in Figure a, tannic acid is at 3409 cm -1 (symmetric stretching vibration of -OH), 1729cm -1 (carbonyl ester group vibration), 1454cm -1 There is a characteristic absorption peak at (-OH in-plane bending), 1321cm -1 and 1199cm -1 The absorption peaks at are attributed to the CO extension of the acid group in tannic acid and the CO extension of polyols, respectively;
[0068] Chitosan is at 1650cm -1 (C=O stretching (amide I)), 1598 cm -1 (NH bending of primary amine), and 1420 cm -1 (-CH 3 There is a characteristic absorption band at 3450cm -1 The characteristic absorption peak at is attributed to the superposition of -OH and -NH vibration absorption peaks. In the infrared spectra of tannic acid and chitosan, the stretching vibration absorption peak of -OH and the bending absorption peak of NH are blue-shifted, proving that the hydroxyl groups in tannic acid and the ammonium ions in chitosan undergo ionic cross-linking reactions to generate physical cross-linking points.
[0069] Depend on Figure 6 As shown in Figure b, there is no obvious change in the absorption bands of the modified foam after modification with chitosan and tannic acid, while the intensity of some absorption bands is weakened, which is attributed to the shielding between the characteristic absorption bands.
[0070] 4. Analysis of adsorption performance
[0071] 1. Effect of the ratio of polyvinyl alcohol to nitrile latex on the adsorption performance of modified foam
[0072] like Figure 7 As shown, when the ratio of polyvinyl alcohol to nitrile latex is 30:70, the maximum adsorption capacity of the modified foam for MB can reach 17.8 mg / g, but the adsorption capacity for MO and RB is lower, only 1.1 mg / g and 5.2 mg / g;
[0073] As the mass fraction of nitrile latex in the modified foam decreases, the adsorption of MB by the modified foam decreases, while the adsorption of MO and RB increases. This is because the electronegativity of the cyanide group in the nitrile latex is much greater than that of the hydroxyl group in the polyvinyl alcohol, and MB is a cation (-NH 2 + ) are more easily attracted by electronegative groups, while MO and RB are anionic (-SO 3 - ) and neutral dyes, the reduced electronegativity is more conducive to increasing their adsorption. In view of this, considering the pore structure and overall adsorption performance of the modified foam, the modified foam with a ratio of polyvinyl alcohol to nitrile latex of 30:70 was selected for adsorption test in subsequent experiments.
[0074] 2. Effect of tannic acid content on the adsorption performance of modified foam
[0075] like Figure 8 As shown, when pure chitosan was used to modify the composite foam of polyvinyl alcohol and nitrile latex, the adsorption amounts of MB, MO and RB by the modified foam were 16.8 mg / g, 12 mg / g and 7.2 mg / g, respectively. Although the adsorption amount of MO was slightly increased, the adsorption of MB was sacrificed.
[0076] With the gradual increase of tannic acid content, the adsorption of MB and RB by the modified foam increased, while the adsorption of MO decreased. This is because the amino groups on chitosan form positive ammonium ions through protonation in water, which have a strong attraction to the anionic dye MO. The phenolic hydroxyl groups on tannic acid are electronegative in the solution, and cross-linked with ammonium ions through Schiff base reaction, which weakens the positive charge of the foam.
[0077] With the increase of tannic acid content, the adsorption of MB and RB by modified foam increased. Figure 8 It can be seen that when the content of tannic acid exceeds 0.3 g, the adsorption amount of MO by the modified foam decreases significantly, and the growth rate of the adsorption amount of RB decreases. Therefore, the tannic acid content is set to 0.3 g, and the ratio of polyvinyl alcohol to nitrile latex is set to 30:70 for adsorption tests in subsequent experiments.
[0078] 3. Effect of initial concentration on adsorption performance of modified foam
[0079] The temperature was set to 40°C and the pH value of the three dyes (MP, MO, RB) was adjusted to 4. The effect of the initial concentration of the dyes on the adsorption performance of the modified foam was studied. The experimental results are shown in Fig. 9 As shown;
[0080] Depend on Fig. 9 It can be seen that with the increase of the initial concentration of the three dyes, the adsorption of MB and RB by the composite foam of polyvinyl alcohol and nitrile latex increases, and the adsorption of MO remains basically unchanged. The adsorption of the three dyes by the modified foam increases.
[0081] At the same time, when the initial concentration was 50 mg / L, the adsorption capacity of the modified foam for MB, MO and RB reached 38.7 mg / L, 32.4 mg / L and 26.4 mg / L, respectively. This is attributed to the fact that the higher the dye concentration, the greater the contact probability with the active sites in the adsorbent and the faster the adsorption reaction rate. According to the principle of equilibrium shift, the greater the saturated adsorption capacity of the foam, the adsorption capacity of MO by the composite foam of polyvinyl alcohol and nitrile latex is very low, with almost no change. This is because the composite foam of polyvinyl alcohol and nitrile latex before modification contains a large number of electronegative groups, and the adsorption capacity of the cationic dye MO is very low. The modified foam not only contains a large number of negatively charged groups such as hydroxyl and cyano groups, but also introduces a large number of amino groups with positive charges, so it has a higher adsorption capacity for the three dyes.
[0082] 4. Effect of temperature on the adsorption performance of modified foam
[0083] The initial concentrations of the three dyes were set to 10 mg / L, and the pH value of the dyes was adjusted to 4. The effect of temperature on the adsorption performance of the modified foam was studied. The experimental results are shown in Fig.10 As shown;
[0084] Depend on Fig.10 It can be seen that with the increase of temperature, the adsorption amount of the three dyes by the composite foam of polyvinyl alcohol and nitrile latex and the modified foam is increased. This is because the adsorption reaction is an endothermic process. The increase in temperature promotes the thermal motion of the dye molecules and increases the probability and efficiency of contact with the active sites of the foam, so the adsorption amount increases.
[0085] However, since the composite foam of polyvinyl alcohol and nitrile latex contains a large number of electronegative groups and has few sites for binding with MO, increasing temperature only slightly increases the adsorption amount. The temperature has a greater effect on the adsorption of MO and RB by the modified foam, with the adsorption amounts increasing by 15.2 mg and 16.0 mg, respectively. When the temperature exceeds 40°C, the adsorption of MO by the modified foam decreases because a reverse reaction occurs after the adsorption amount reaches saturation.
[0086] 5. Effect of pH value on adsorption performance of modified foam
[0087] The initial concentrations of the three dyes were set to 10 mg / L and the temperature was set to 40°C to study the effect of pH on the adsorption performance of the modified foam. The experimental results are as follows: Fig.11 As shown;
[0088] Depend on Fig.11 It can be seen that with the increase of pH value, the adsorption amount of MB by the modified foam increases, while the adsorption amount of MO and RB decreases. When the pH value is 4, the adsorption amount of MO and RB by the modified foam is 25.4 mg / g and 22 mg / g respectively. This is because when the pH value is low, the amino groups in chitosan produce a large number of positive ammonium ions through protonation, which is conducive to the adsorption of MO and RB with anionic groups.
[0089] At the same time, the adsorption amount of MB by the modified foam is still 25.1 mg / g. This is because the modified foam and tannic acid contain a large number of electronegative groups. With the increase of pH, the amino groups in chitosan are deprotonated, the adsorption amount of MO is weakened, the hydrogen ion concentration is reduced, and the competitive adsorption with cations is weakened, resulting in an increase in the adsorption amount of MB.
[0090] In the prior art, the dissociation of phenolic hydroxyl groups in tannic acid under alkaline conditions causes a sharp decrease in the adsorption capacity of the modified foam for MO after the pH increases. However, since RB contains anionic and cationic groups, the adsorption capacity of the modified foam for RB decreases less.
[0091] 6. Effect of contact time on adsorption performance of modified foam
[0092] The initial concentrations of the three dyes were set to 10 mg / L, the temperature was set to 40 °C, and the pH value was set to 4. The effect of contact time on the adsorption performance of the modified foam was studied. The experimental results are shown in Fig.12 As shown;
[0093] like Fig.12 As shown, with the extension of contact time, the adsorption amount gradually increased and eventually tended to equilibrium;
[0094] Among them, MO reaches equilibrium the fastest, followed by RB, and MB takes the longest time to reach adsorption saturation. The reaction rates are fast at first and then slow. This is because there are many active sites that can be adsorbed in the initial stage of the reaction, and as the reaction continues, the active sites are gradually consumed, resulting in an increase in the adsorption amount and a decrease in the adsorption rate.
[0095] In summary
[0096] The present application prepares polyvinyl alcohol and nitrile latex composite foam by solution blending and mechanical foaming, and uses chitosan and tannic acid as modifiers to modify the foam by an impregnation method, thereby preparing a modified foam with dye adsorption capacity. The adsorption performance of the modified foam is then tested, and the results show that:
[0097] 1. The pore structure of the composite foam of polyvinyl alcohol and nitrile latex is composed of interconnected macropores and small pores. As the mass fraction of nitrile latex increases, the pore size increases, the density decreases, and the specific surface area increases. When the ratio of polyvinyl alcohol to nitrile latex is 30:70, the compatibility of polyvinyl alcohol and nitrile latex is the best. At the same time, the modifier made of chitosan and tannic acid can adhere tightly to the surface of the composite foam of polyvinyl alcohol and nitrile latex, will not block the pores, and allow the liquid to flow inside the composite foam of polyvinyl alcohol and nitrile latex, and the modified After modification, the proportion of carbon and nitrogen elements on the surface of the foam decreased, the proportion of oxygen elements increased, and the surface element density was greater, indicating that the modifier was well combined with the composite foam of polyvinyl alcohol and nitrile latex, and the modifier formed physical crosslinking points through the reaction of ammonium ions formed by the protonation of the hydroxyl groups in tannic acid and the amino groups in chitosan. No new characteristic peaks were generated before and after modification. Therefore, the modifier was bonded to the composite foam of polyvinyl alcohol and nitrile latex through physical action, which again indicated that the modifier was well combined with the composite foam of polyvinyl alcohol and nitrile latex;
[0098] 2. The composite foam of polyvinyl alcohol and nitrile latex has good adsorption performance for cationic dye MB, and low adsorption capacity for anionic dye MO and neutral dye RB. When modified with pure chitosan, the adsorption capacity for MB, MO and RB is 16.8 mg / g, 12 mg / g and 7.2 mg / g respectively. After the addition of tannic acid and chitosan undergo ion cross-linking reaction, the stability of the modifier is significantly improved. When the tannic acid content is 0.3 g, the comprehensive adsorption performance for the three dyes is the best.
[0099] At the same time, as the initial concentration of the dye increases, the adsorption capacity of the modified foam for each dye increases. When the initial concentration is 50 mg / L, the adsorption capacity of the modified foam for MB, MO and RB reaches 38.7 mg / L, 32.4 mg / L and 26.4 mg / L respectively.
[0100] The temperature has a greater effect on the adsorption of MO and RB by the modified foam, and the adsorption amounts increased by 15.2 mg and 16.0 mg respectively;
[0101] And as the pH value increases, the adsorption of MB by the modified foam increases, while the adsorption of MO and RB decreases. At pH 4, due to the protonation of the amino groups of chitosan, the adsorption of MO and RB by the modified foam is high. The hydrogen ions in the acidic condition compete with MB for adsorption, resulting in a low adsorption of MB.
[0102] At the same time, with the extension of contact time, the amount of dye adsorbed by the modified foam gradually increased and eventually tended to equilibrium, among which MO reached equilibrium the fastest, followed by RB, and MB took the longest time to reach adsorption saturation, and the reaction rates were fast at first and then slow.
[0103] In summary, the modified foam finally has an adsorption capacity of more than 20 mg / g for the three dyes, which can well adsorb the active dyes in the wastewater, has a significant effect on the purification of the water environment, reduces pollution, and has good application prospects.
[0104] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A method for modifying a composite foam of polyvinyl alcohol and nitrile latex, characterized in that: The following steps are involved: Step A, adding chitosan powder into deionized water containing glacial acetic acid and stirring to prepare a chitosan solution; Step B, adding tannic acid into deionized water to dissolve it to prepare a tannic acid solution; Step C, mixing the tannic acid solution and the chitosan solution, and cooling to room temperature to prepare a modifier for standby use; Step D, immersing the composite foam of polyvinyl alcohol and nitrile latex in a modifier, repeatedly squeezing, standing and drying, to obtain a modified foam; The preparation process of the polyvinyl alcohol and nitrile latex composite foam is: Step 1, add polyvinyl alcohol and deionized water into a beaker, stir and cool to room temperature to prepare a polyvinyl alcohol solution for standby use; Step 2, add polyvinyl alcohol solution and nitrile latex to another beaker, stir, and cool to room temperature after the reaction is completed to prepare a blended solution; Step 3, adding sodium dodecyl sulfate to the blended solution, stirring and foaming, and then pouring into a silica gel mold and freezing to prepare a sample; Step 4, thawing the sample in anhydrous ethanol, and then drying to obtain a composite foam of polyvinyl alcohol and nitrile latex; In step 3, an IKA digital stirrer was used to stir and foam for 5 min at 1200 rpm, the freezing temperature was -20°C, and the freezing time was 24 h; In step D, the extrusion times are 3 times with an interval of 6 hours, the standing time is 12 hours, the drying temperature is 50° C., and the drying time is 12 hours.
2. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step 1, polyvinyl alcohol is 10 g, deionized water is 80 g, and the mixture is stirred at 95° C. using a magnetic rotor for 2 h.
3. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step 2, the stirring time is set to 1 hour, and the amount of polyvinyl alcohol solution added is 30g, 40g, 50g, 60g or 70g, and the amount of nitrile latex added is 70g, 60g, 50g, 40g or 30g.
4. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step 4, the thawing time is 12 hours, the drying temperature is 50° C., and the drying time is 24 hours.
5. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step A, chitosan powder is 2 g, glacial acetic acid is 2 mL, deionized water is 100 mL, the stirring temperature is 50° C., and the stirring time is 2 h.
6. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step B, tannic acid is 0.6 g, deionized water is 100 mL, and the temperature is room temperature.
7. The method for modifying a polyvinyl alcohol and nitrile latex composite foam according to claim 1, characterized in that: In step C, the stirring temperature is 50° C. and the stirring time is 0.5 h.
Citation Information
Patent Citations
Biodegradable hydrophilic oleophobic foam with adsorption function
CN113388154A
Method for preparing low-shrinkage metal-polyphenol network foam through freeze thawing and drying and product
CN118240271A
Cosmetics comprising a porous foam and a cosmetic composition impregnated therein
KR1020160017594A